Optimalisasi Pendapatan UMKM Melalui Edukasi Keaslian Uang Rupiah di Desa Sirnabaya - Ery Rosmawati; Ujang Suherman; Dexi Triadinda; Rengga Madya Pranata (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve the community's understanding and skills in recognizing the authenticity of rupiah currency, especially among MSMEs. With a better understanding, it is hoped that MSMEs can avoid losses due to questionable currency and optimize their income. The community service method used was a focus group discussion to identify the problems, potential, and needs of MSMEs in Sirnabaya Village. The immediate impact of this activity is an increase in early detection skills for counterfeit money in the community. In the long term, it is hoped that this will reduce the rate of counterfeit money circulation in the target area.